Air-coupled guided wave inspection of aerospace composites - Low, Jun Feng (Nanyang Technological University, 2021)
Composites are known to have highly tunable properties to meet the requirements for a wide variety of applications. Most notably, they have been heavily utilised in aircrafts. Non-invasive and non-destructive testing (NDT) is required to monitor the structural health of such vehicles. Currently, water-jet coupled ultrasound testing is used for the non-destructive testing of aircraft. However, the use of water-jet NDT to inspect ¬honeycomb structures in aircrafts gives rise to a danger of water ingression that may induce degradation within the composites. Therefore, the implementation of a non-contact NDT technique for the purpose of aircraft inspection is desirable.